Grammatical Disagreement and Agreement in Guaymí Spanish - Valverde Rodríguez, Hazel (2025)
A description is presented of the phenomenon of agreement and disagreement of gender and number in the noun phrase of the Spanish spoken by the Guaymí people in Costa Rica. Oral samples were collected from four Guaymí women and transcribed; the corpus was organized, and the data analyzed. The gender and number discordances in the Spanish of these speakers can be explained as an influence of Guaymí, since this language is not marked morphologically for gender, and, in the case of number, morphological marking tre~dre is optional.